EFFECT OF UROKINASE GENE-KNOCKOUT ON GROWTH OF MELANOMA IN EXPERIMENT - E. M. Frantsiyants; I. V. Kaplieva; E. I. Surikova; I. V. Neskubina; V. A. Bandovkina; L. K. Trepitaki; N. S. Lesovaya; N. D. Cheryarina; Yu. A. Pogorelova; L. A. Nemashkalova (Сибирский научный медицинский журнал, 2019)
The purpose of the study was to reveal special features of the В16/F10 melanoma growth in urokinase (uPA) gene knockout mice with and without chronic neurogenic pain (CNP). Material and methods. The study included male and female С57ВL/6 mice (n = 102) and C57BL/6-Plautm1.1BugThisPlauGFDhu/GFDhu mice with uPA gene knockout  (n = 48). Mice of the main subgroups underwent subcutaneous transplantation of В16/F10 melanoma 2 weeks after bilateral ligation of sciatic nerves (CNP model); mice of the same strain with standard melanoma transplantation served as controls. Results and discussion. Survival of uPA gene knockout mice did not differ from that of normal animals – 1.5 times higher in females than in males (p < 0.05), with melanoma onset in gene-deficient mice a week earlier. The dynamics of tumor growth had pronounced gender differences: in females, the tumor did not grow and its maximal volume prior to death was 1.0 cm3, while tumors in males were characterized by an active growth with two peaks of volume increase (weeks 2 and 4). Melanoma was weakly metastatic – solitary metastases to the lungs (in females) or no metastases, but pulmonary and heart hemorrhages were noted (in males). CNP decreased the survival of uPA gene knockout females, as well as of normal animals, but did not influence the survival of males; primary tumors in genedeficient mice appeared a few days later than in controls but their growth was more intense, with diminished gender differences. Increased metastasis was manifested by the initiation of metastatic lesions to the lungs and liver in males, with maintained pulmonary hemorrhages, and by increased number of metastatic foci in the lungs together with the appearance of pulmonary hemorrhages in females. Conclusions. The influence of uPA gene knockout on the course of В16/F10 melanoma differs in male and female mice. CNP enhances malignant tumor growth, diminishing gender differences, and activates melanoma metastasis.